Optimum arrangement of braces in jacket platform based on strength and ductility. (May 2020) - Tabeshpour, Mohammad Reza; Fatemi, Mani
Abstract: Nonlinear behavior of jacket platforms is important in both design and rehabilitation issues that depends on the bracing arrangement. Both ductility and strength of the structures derived from pushover analysis are highly related to configuration of the braces. Considering a suitable criterion such as constant weight or constant stiffness and period of the structure in all arrangement cases, one can compare the capacity curves and find the best configuration. In this paper a simple logical method for investigating the strength and ductility of the jacket structure is presented, it is shown that global geometry and configuration of the braces are very important and effective in both strength and ductility parameters. Three parameters, normalized strength, normalized ductility and a combination of these two parameters are defined in order to have an engineering and practical index for comparing the results. At the end of the numerical discussion, the optimum configuration can be found. Such an investigation is very important in the initial design stage. Also, in assessment of existing platforms, it is very important to find the reliable strength and ductility of the structure. Such a study gives a deep view of this issue as well. Highlights: A simple method for comparing different bracing configurations of offshore jacket platforms by is introduced. Normalized strength; ductility and a combination of these two parameters are defined as an index for comparing the results. At the end of the numerical discussion, the optimum configuration can be find.